Trace metal enrichment observed in soils around a coal fired power plant in South Africa - Amaris Dalton; Gregor T. Feig; Kaylin Barber (Clean Air Journal, 2018)
A site assessment was conducted at a coal fired power plant in South Africa to determine whether surrounding soils were being enriched with trace metals resulting from activities at the power plant. It was found that deposition of fly ash from the flue stacks and the ash dump along with deposition of coal dust from the coal stock yard were the activities most likely to lead to such enrichment. Eighty topsoil samples were gathered and analysed for total metal content. Results were interpreted within the context of background values. It was found that concentrations of As, Cu, Mn, Ni and Pb exceeded local screening levels, but only As and Pb could be confidently attributed to anthropogenic intervention and actual enrichment.